An extension of the Dang Van fatigue criterion to finite life predictions - Korsunsky, A; Peridas, G; Hills, D (2009)
An extension to Dang Van's crack initiation and Sines' failure criterion is formulated permitting finite life predictions to be made. This draws on the recent results regarding the relationship between the Dang Van criterion, Sines' criterion and Goodman's rule. The approach is applied to a set of experimental data obtained by Socie et. al. [1]. The results show a good correlation between predictions and experiment, suggesting that the Dang Van criterion modified in this way can usefully serve to predict HCF life. In order to establish which of the two criteria performs best, data spanning a wider range of R-ratios is required.